Male peer support, hunting, and separation/divorce sexual assault in rural Ohio - Hall-Sanchez, Amanda K. (Critical criminology, 2014)
Male peer support is one of the most powerful determinants of woman abuse across the globe. Still, key gaps remain in rural male peer support literature, such as overlooking the importance of hunting as a public male-bonding ritual that serves to reinforce abusive behaviors against women in private settings. The main objective of this article is to present findings from an exploratory, qualitative, back-talk study of twelve women’s experiences of separation/divorce sexual assault in rural Ohio. The results reveal a relationship between rural hunting subculture dynamics and core elements of male peer support (i.e. frequent drinking with male friends, informational support, attachment to abusive peers, and patriarchal masculine identity). Male peer support in hunting subcultures coupled with the availability and access to ‘legitimate’ weapons creates a fertile breeding ground for woman abuse in some rural communities.